GIRLS PARTY DRESSES WITH CEMPAKA FLOWER BATIK MOTIFS - Nafiah, Anisa; Nurarfah, Ismy Putra (Indonesian Institute of the Arts Surakarta, 2024)
The purpose of creating this work is to apply the Cempaka Flower motif into party dresses for girls. The methods used in making this work include expression, technique, and creation. The process of making this work consists of: the initial process using the batik tulis technique, then proceed with the coloring process in the form of dyed caps with synthetic dyes, namely with remasol dye, and using silk cotton fabric that is smooth and soft, therefore it is comfortable to use for girls’ party fashion works. The creation of this work resulted in four different types of girls' party dresses for ages 6-12 years. In this work, there are four different titles for each work that has been made, namely Lalita, Arabelle, Nayara, and Wening. Each of which has the meaning and expectations of the creator for each work created. The meaning of the work inspired by the cempaka flower is to present the leadership spirit of a woman, have a beautiful shape and smell good, present a woman who has a beautiful and charming appearance and has a strong character and a very attractive personality. The presence of a woman with a leadership spirit is able to present a nurturing feeling like the long petals of a chrysolite flower and are able to cover many people and other things. The end result of the creation of this work is that it is suitable for girls' party dresses aged 6-12 years and is suitable for attending birthday parties, garden parties, and various other formal events.